The Chemistry Teacher Activities on The Training of Project Based Learning Teaching Materials Digitalisation - Suryani, Okta; Sari, Trisna Kumala; Riga, Riga; Mawardi, Mawardi; Yuhelman, Nofri; Nasra, Edi; Velly, Aglin; Rahmad, Nafisah Yulia (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This activity is the second year of community service which is a continuation of training activities and making digital teaching materials to support project-based learning (PjBL) in sekolah penggerak for chemistry teachers in Padang city. This second year of community service activities has the theme of training to digitise project-based learning teaching materials developed at the Chemistry Musyawarah Guru Mata Pelajaran (MGMP) in Padang city. This activity aims to provide direction to Padang city chemistry teachers in implementing digital teaching materials. This community service was carried out in the lecture building of FMIPA Universitas Negeri Padang on 9 August, 16 August, and 23 August 2024. The implementation methods carried out in this community service activity are: (1) conducting a needs analysis, knowing the situation of teachers towards the implementation of PjBL-based learning through questionnaires distributed, (2) delivering material to community service participants related to PjBL and an overview of teaching materials that have been designed using the PjBL learning model explained by the speaker, then (3) delivery of materials and discussions related to differentiated learning with the PJBl learning model, and (4) delivering material related to the digitalisation of project-based teaching materials or PjBL using liveworksheet. The results of the service activities carried out can provide motivation, provide experience, and understanding for Padang city chemistry teachers regarding the digitalisation of project-based learning teaching materials so that chemistry teachers in Padang city can prepare digital chemistry teaching materials, especially with liveworksheets using the PjBL model that can assist learning activities so that learning can run effectively and efficiently in accordance with the demands of the curriculum and the times.